2013
DOI: 10.2337/db12-1771
|View full text |Cite
|
Sign up to set email alerts
|

More Than 20 Years of Registration of Type 1 Diabetes in Sardinian Children

Abstract: We analyzed Sardinian registry data to assess time trends in incidence rates (IRs) of type 1 diabetes during the period 1989–2009 (2,371 case subjects 0–14 years of age). Poisson regression models were used to estimate the effects of sex, age, period of diagnosis, and birth cohorts. IR was 44.8 cases/100,000 person-years (95% CI 43.1–46.7). The annual increase was 2.12% (1.45–2.80; test for linear trend, P < 0.001). For boys, the increasing trend was evident up to 5 years of age and for girls up to 8 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
1
28
1
Order By: Relevance
“…One possible explanation is a growing trend for autoimmunity in general. However, in contrast to preceding studies (14,15,16,17,18), in our cohort the prevalence data for the much more frequent autoimmune diseases type 1 diabetes mellitus and vitiligo did not change relevantly over the years 2009-2011, but the triggering and/or causative agents in rare AD may differ from those more common disorders.…”
Section: European Journal Of Endocrinologycontrasting
confidence: 52%
See 1 more Smart Citation
“…One possible explanation is a growing trend for autoimmunity in general. However, in contrast to preceding studies (14,15,16,17,18), in our cohort the prevalence data for the much more frequent autoimmune diseases type 1 diabetes mellitus and vitiligo did not change relevantly over the years 2009-2011, but the triggering and/or causative agents in rare AD may differ from those more common disorders.…”
Section: European Journal Of Endocrinologycontrasting
confidence: 52%
“…An increasing incidence has been observed in AD (1,2,4,6,8) and several other autoimmune-mediated disorders in recent years, including celiac disease (13), type 1 diabetes (14,15,16,17,18), and multiple sclerosis (19). Diverse genetic variations predispose to autoimmune AD (20,21,22).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…The youngest age group was once believed to have the fastest growth in T1D incidence . Recently, however, quite a few studies reporting 5 to 9 years or 10 to 14 years as the age group with the greatest annual increase seem to have conflicted with the mainstream finding that the youngest age group, 0 to 4 years, exhibits the most substantial increase in T1D incidences . Although most epidemiological investigations focus on the age group of 0 to 14 years and data of patients with T1D aged over 14 years are insufficient, studies conducted in the United Kingdom, Mexico, Israel, and the United States have revealed a significant increment in T1D incidences for youth aged 15 to 34, 15 to 19, 15 to 17, and 15 to 19 years respectively.…”
Section: Epidemiologymentioning
confidence: 99%
“…T1D was initially recognized as a chronic disease among children and young adolescents, but over time, the perspective that T1D can occur at any age has been gradually accepted . The incidence of childhood T1D has been growing globally since the past few decades though stagnation has also been observed in a small number of regions around the world …”
Section: Introductionmentioning
confidence: 99%
“…The authors found a progressive decrease in the annual incidence rate over the study period (2009–2013). According to previous studies, the incidence rate of Type 1 Diabetes among children (0–14 years of age) had been increasing [25] over the past 20 years. Moreover, a similar study carried out in Friuli-Venezia Giulia (a region in northern Italy) [6] found an almost stable incidence over the same period, excluding the first year of registration (2010).…”
mentioning
confidence: 99%